Decoupling Strategy and Modular Design for Loosely Coupled Organizations - Jing Zhang; Fengyan Li; Xiangmin Zhang (Discrete Dynamics in Nature and Society)
Under the technological innovation network, loosely coupled organizations featured by weak connections and relative independence have formed through the dynamic division of labor and knowledge sharing of enterprises. The loosely coupled organizations greatly enhance cooperation performance, but face problems such as poor flexible matching between partners and low innovation efficiency. Meanwhile, modular organizations can connect with other organizations to realize a specific operational goal via contracts and carry prominent features such as collaborative innovation, adaptive division of labor, and dynamic capabilities, offering an effective network governance model for collaboration between enterprises. Based on the two dimensions (looseness and coupling) between organizations, this paper uses the design dependency matrix (DDM) to map demands for functional/design modules, under the division of labor within products and the decisions on product modules, and preliminarily decouple the functional/design modules. Based on clustering DDM, a decision structure matrix (DSM) was constructed, and the clustering decoupling algorithm was adopted to create clustering design structure modules. Referring to these clustering modules, intraproduct division of labor was performed to realize the modular cooperation between organizations.